The Intel microprocessors 8086/8088, 80186/80188, 80286, 80386, 80486, Pentium, and Pentium Pro processor - Brey, Barry B. (Prentice Hall, 1997)
This fourth edition of "The Intel Microprocessors 8086/8088, 80186, 80286, 80386, 80486, Pentium, and Pentium Pro Processor: Architecture, Programming, and Interfacing" is a practical book for anyone interested in all programming and interfacing aspects of this important microprocessor family